PERBANDINGAN JENIS HIJAUAN RAWA PADA PAKAN KOMPLIT GRANUL TERHADAP KANDUNGAN NUTRISI DAN KECERNAANYA - Achmad Jaelani; Abd Malik; Gusti Khairun Nimah; Muhammad Syarif Djaya (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2019)
The study aimed to analyze the type of swamp forage and its combination in granule complete feed products for their nutrient content and digestibility. This study have been done on Juli until September, 2018 in Field Laboratory at Bentok Kampung-Tanah Laut District. Randomized Block Design was used in this research with 3 treatments and 4 replications. Twenty goats aged 1.5-2 years with a weight ranging from 15-19 kg were used in this study. Data were analyzed by Analysis of varian and if there is significant difference then the Duncan Multi Range Test (DMRT) is continued. The results of the study show that swamp forage kalakai (Stenochlaena palustris), and purun tikus (Heleocharis dulcis Burm) significantly different to the crude protein content, crude fiber, crude fat, ADF and NDF fiber fraction. The complete granule feed on the basis of a combination of forage swamps and legumes affects the digestibility of organic matter and crude protein. The low content of tannin in swamp forages has not been able to optimally protect crude protein in complete granule feed.